The Effectiveness of Public Communication by the North Sumatra Tourism Office on the "Sumut Tourism Festival 2024" Event Calendar to Strengthen Tourism in North Sumatra Among Students of Politeknik Negeri Medan - An Nisa Dian Rahma; Putri Sosanti Sembiring; Dyah Seruni Rizqiana (Journal Analytica Islamica, 2025)
This study aims to analyze the effectiveness of public communication conducted by the North Sumatra Tourism Office at the "Sumut Tourism Festival 2024" event in strengthening the tourism sector in the province, with a focus on the perceptions of students of the D-IV MICE Study Program at the Medan State Polytechnic. The specific target to be achieved is to identify effective public communication strategies in increasing student participation and interest in visiting North Sumatra tourism, as well as providing recommendations for improving future communication strategies. The research method used is a quantitative approach with a survey using a questionnaire distributed to students. The data obtained will be analyzed using descriptive and inferential statistics. The results of the study indicate that public communication conducted by the North Sumatra Provincial Tourism Office through the "Sumut Tourism Festival 2024" has proven effective in strengthening the regional tourism sector. This effectiveness is seen from the positive and significant influence between public communication (X) on strengthening tourism (Y), evidenced by the calculated t value (9.825) > t table (1.974) and Sig. 0.000 < 0.05. This means that the more effective the public communication is, the greater the strengthening of public interest and participation, especially MICE students at the Medan State Polytechnic, in the tourism sector.